High‐tuning‐range CMOS band‐pass IF filter based on a low‐Q cascaded biquad optimization technique. (23rd October 2014) - Monsurrò, Pietro; Pennisi, Salvatore; Scotti, Giuseppe; Trifiletti, Alessandro
Summary A design procedure for high‐order continuous‐time intermediate‐frequency band‐pass filters based on the cascade of low‐Q biquadratic cells is presented. The approach is well suited for integrated‐circuit fabrication, as it takes into account the maximum capacitance spread dictated by the available technology and maximum acceptable sensitivity to component variations. A trade‐off between noise and maximum linear range is also met. A novel, wide‐tuning‐range transconductor topology is also described. Based on these results, a 10‐pole band‐pass filter for a code division multiple‐access satellite receiver has been designed and tested. The filter provides tunable center frequency (f0) from 10 to 70 MHz and exhibits a 28‐MHz bandwidth around f0 = 70 MHz with more than 39‐dB attenuation at f0/2 and 2f0. Third‐order harmonic rejection is higher than 60 dB for a 1‐Vpp 70‐MHz input, and equivalent output noise is lower than 1 mVrms. The circuit is fabricated in a 0.25‐µm complementary metal oxide semiconductor process, and the core consumes 12 mA from a 2.5‐V supply, offering the best current/pole ratio figure. The die area resulted to be 0.9 × 1.1 mm2. Copyright © 2014 John Wiley & Sons, Ltd.